Implementation of Classical Guidance with the Problem Based Learning Method in Improving Student Learning Independence - Farenti Farenti; Amrina Jaya; Fadhlina Rozzaqyah (Indonesian Journal of Education Research (IJoER), 2025)
Purpose of the study: The purpose of this study was to determine the extent to which the implementation of classical guidance services with the Problem Based Learning (PBL) method can improve the learning independence of class IX students at State Junior High School 7 Palembang. Methodology: This research is a guidance and counseling action research (PTBK) which is a research on an action carried out in a class with the aim of improving the quality of the guidance and counseling service process. The process of implementing PTBK is the same as implementing action research. Main Findings: Data obtained from 36 students showed very positive results. Based on pretest data, the average score of student learning independence was 50 out of an ideal score of 100. After implementing PBL-based classical guidance services, the average posttest score increased to 88.6, indicating a significant increase. Novelty/Originality of this study: With proper implementation, this approach is expected to significantly improve the learning independence of students of State Junior High School 7 Palembang. In addition, this approach can also help BK teachers design more creative and appropriate services for students' needs, as well as being an example for other schools in an effort to improve the quality of learning.